Flipped learning en los aprendizajes de inglés en estudiantes del primer nivel de las carreras de idiomas extranjeros en la Universidad Nacional de la Amazonía Peruana Iquitos 2022 - Lazo Ramírez, Lila (2023)
The objective of this research was to assess the effectiveness of a student educative program focused on flipped learning on English learning in first level students of Foreign Language career at the National University of the Peruvian Amazon, Iquitos 2022. The research type has been evaluative with field research, contemporary transectional, univariate, and quasi experimental designs with pre-test, posttest and control group. The population and sample were made up of 58 students. Data collection tools were valid and reliable comprehension tests, performance tests and rubrics. Posttest outcomes present that the experimental group outperformed the control group as their mean scores were higher (14,110 > 10,040). It was also the case for its dimensions: Listening (13,333 > 7,810), speaking (13,426 > 10,190), reading (14,530 > 9,700), and writing (15,150 > 12,490). In conclusion, there is statistically significant difference in students’ English performance after developing flipped learning-based teaching as p- value = < α = 0,05.